Incorporating sustainability into the strategy of HEI: a systematic literature review - Simaens, A. (7th Responsible Management Education Research Conference, 2020)
Higher Education Institutions (HEIs) can play important role in the path towards sustainable development (Walter Leal Filho 2011), while being highly shaped by the sustainability agenda (Franco et al. 2019). As Leal Filho (2011, p. 24) puts it, “university blueprints (or strategies), declarations or action plans are useless, unless they can be backed up by concrete action in one or more of the following areas: (a) curriculum greening; (b) campus operations; (c) research; (d) extension (i.e. continuing education and further education programmes); (e) concrete projects”. Franco et al (2019) alerts to the fact that unless the attempts to incorporate sustainability into policies, curriculum and practices of HEI are strategically supported by a coordinated and integrated governing approach, it is not effective. There is a lack of empirical studies exploring the integration of sustainability into strategic management (Engert et al. 2016). Still, one can find cases of sustainable strategies in HEI (e.g. Mori Junior et al. 2019; Paletta and Bonoli 2019; Purcell et al. 2019; Ramísio et al. 2019), as well as at HEI at a national level (Bieler and McKenzie 2017; Do 2020; Farinha et al. 2019; Larrán et al. 2016; Parvez and Agrawal 2019; Shawe et al. 2019). Still, there is a lack a systemic approach to the way sustainable development is integrated into HEI (Shawe et al. 2019), and as Leal Filho et al. (2019) concluded, more has to be done by HEI in terms of strategic planning for sustainable development. Then, it becomes crucial to understand the extent to which are HEI incorporating sustainability into their strategic management process. To explore the research question “What do we know about the incorporation of sustainability into the strategy of HEI?”, the methodology includes a systematic literature review of the literature. The search equation (strateg* AND sustainab* AND higher education) generated 762 journal articles in SCOPUS database. Based on this search in title, abstract and keywords, the analysis followed a multi-stage exclusion process until the final sample of papers. The final sample of papers was coded in MAXQDA according to the following categories: 1) Governance (leadership, decision-making, performance measurement); 2) Core activities: a) teaching, b) research, c) campus operations, and d) outreach. Preliminary results show that there is a growing number of papers exploring this topic, and that the dominant outlets for this research are the International Journal of Sustainability in Higher Education, Sustainability, and the Journal of Cleaner Production. The dominant areas are Social sciences, Business, management and accounting, and Environmental Science. This research takes stock of the literature that crosses strategy and sustainability in the context of higher education, while identifying gaps in the literature and suggesting new avenues of research in this field.